Ajaran Syeikh Nawawi al-Bantani Tentang Pendidikan Akhlak Anak - Ilyas, M. Azizzullah (AR-RIAYAH : Jurnal Pendidikan Dasar, 2018)
Cultural and technological developments have an effect on children, positive and negative effects, these developments also effect in children's morality toward his parents. This erosion of moral values is interesting to study. We tried to see the moral values through the teachings of Sheikh Nawawi al-Bantani, a classical Indonesian scholar, his teachings goals and relevance for contemporary education. This research is a qualitative research by analyzing the main sources of Tafsir Marahil labid and Maraqi Ubudiyah Syarah Bidayah Hidayah. This study concludes that the teachings of Sheikh Nawawi Al-Bantani lead to the form of moral competence that does not stop at morality at the level of cognition and emotion, but rather integrates it with moral actions. His teachings combine adherence to God and devotion to parents as two things that cannot be separated but still make obedience to God as the main foundation